Conductividad eléctrica de carbón térmico a diferente humedad y tamaño de grano - Bautista, N; González, E; Bautista-Ruiz, J; Peña-Rodríguez, G (Uptc, 2012)
This paper reports the experimental development for two thermal coal samples taken from the metropolitan  quartering, drying and grinding with a mechanical grinder. Subsequently it was determined the physicochemical composition by means of near or immediate analysis, and, finally, it was measured the electrical conductivity at different grain sizes and with different percentages of humidity, observing the  input on the sample, and the response or potential output of the same(the four tips method).